International recomendations for improvement of competencies in compulsory education in Spain - Alberto Vaquero García (ADIDE Federación, 2018)
Seventeen years ago, in 2000, Spain participated in the first PISA assessment. Four education reforms, which have undoubtedly affected the results of the assessment of our 15-year-old students in reading, mathematics and science, have been approved during this period in Spain. The objective of this article is to review the Spanish situation in the PISA programme, in order to find out if the indicators obtained could have been improved, as well as to provide a set of recommendations for the coming years, to try to correct the detected deficiencies in our assessments. From the analysis carried out we can point out that, in spite of significant improvements in the results, we can still observe relevant differences depending on the type of Centre that has been evaluated, on the existence or non-existence of itineraries, on the incidence of failure in school and on the regions.